Improving Research- and Innovation Collaboration between Healthcare Organizations and Business Actors - A Case Study at Sahlgrenska University Hospital - Hjärtmyr, Gustaf; Uddenstig, Tilda (My University, 2022)
When the need for more efficient ways to deliver healthcare increases due to factors such as demographic changes or government pressure to cut costs, research and innovation within healthcare become more and more important to meet these challenges. The Covid-19 pandemic has further highlighted the need for research and innovation when new diseases emerge. However, the complexity surrounding the healthcare sector makes research- and innovation sometimes complicated. There are significant gains if the healthcare organizations and other actors in the ecosystem collaborate in order to overcome the complexity of innovation within healthcare. Nevertheless, collaborative research- and innovation initiatives within healthcare are often argued to be underutilized. Some difficulties often brought up are the issues regarding how the actors can meet each other, how rules and regulations affect opportunities to collaborate, and how the organizational setting of healthcare organizations differs from the business actors, further complicating co-creation. Therefore, the purpose of this thesis is to provide insights into barriers, facilitators, and potential improvement for research- and innovation collaboration between healthcare and business actors, with a focus on the healthcare providers perspective. The research approach used was a qualitative single-case study at Sahlgrenska University Hospital. Empirical data was collected through interviews with employees at Sahlgrenska University Hospital as well as different actors within the healthcare innovation ecosystem. The data were then analyzed in relation to a theoretical framework based on the notion of open innovation and four levels of analysis: socio-political, inter-organizational, organizational, and intra-organizational. Findings show that barriers and facilitators exist on different levels and these need to be managed to improve collaborative initiatives. While the barriers existing at a socio-political level with for example different laws heavily influencing what is allowed to do, these barriers cannot be removed but rather needs to be handled, so the influence of them are reduced. On the other levels, healthcare organizations have better opportunities to remove barriers, including finding clearer entry points and forums to meet, changing the organizational culture, managing the ambidexterity problem, and utilizing support functions. Lastly, it was identified that tensions exist between research and other innovation activities and that the size of companies affect opportunities to engage in collaborative activities with the healthcare sector.